Avaliação da eficiência de tecnologias de proteção da ictiofauna em empreendimentos hidrelétricos - Ana Alice Cesário Porto (2017)
Hydroelectric Power Plants (HPP) are the most important source of energy in Brazil. Since the beginning of the XX Century, the Electric Sector has passed the environmental problems that were gradually surpassed or mitigated. Among the questions that were open, related to those the aquatic fauna, still stand out the icthyofauna. The literature lists that the main anthropic factor is a loss of biodiversity and the change of the habitats. The dealerships have been striving to mitigate the negative impacts of HPP reservoirs on fish community. One of the most discussed impacts among the specialists is the interception of migratory fish routes, which leads to interference of the fishing community. Attention towards this impact is extremely relevant considering the diversity of fish species in Brazilian rivers and their importance in the local culture and subsistence of people who lives near the river and in the economy (Junho, 2008). This project has as purpose to show the impacts from the HPP implantation on the fish community and in their respective migrations actions through detailed analyzes, preventive studies and applications of viable technological alternatives during the design phase, aiming for operational improvement (Services of operation and maintenance O&M) and its environmental viability. A case study of Retiro Baixo HPP is shown where improvements and technological mechanisms proposed during the design phase resulted in a significant improvement in the system. In order to achieve this result, the main locations where fish mortality could occur and respective solutions were verified. Possible conditions for machine shutdowns and maintenance of the systems were studied. The gain from the proposed modifications were evaluated based on the operational facility and the reduction of fish mortality in the HPP